Fertility and Family Policies in Central and Eastern Europe after 1990 - Frejka, Tomas; Gietel-Basten, Stuart (Comparative population studies, 2016)
This paper examines fertility and family policies in 15 Central and East European (CEE) countries to establish firstly, likely directions of cohort fertility trends for the coming decade; and secondly, to provide an overview and analysis of family policies in CEE countries, and to assess their impact on cohort fertility trends. Demographic analysis suggests that the cohort fertility decline of the 1960s cohorts is likely to continue at least among the 1970s birth cohorts; stagnation cannot be ruled out. Births that were postponed by women born in the 1970s were not being replaced in sufficient numbers for cohort fertility to increase in the foreseeable future, and shares of low parity women (childless and one child) were larger than shares of high parity women among the late 1960s cohorts than in older cohorts. Also, childbearing postponement which started in the 1990s is reflected in dramatic changes of childbearing age patterns. As period fertility rates have been increasing in the late 2000s throughout the region an impression of a fertility recovery has been created, however the findings of this project indicate that no such widespread childbearing recovery is underway. For the first time ever an overview and analysis of CEE family policies is conceptualized in this paper. It demonstrates that fertility trends and family policies are a matter of serious concern throughout the region. The following family policy types have been identified: comprehensive family policy model; pro-natalist policies model; temporary male bread-winner model; and conventional family policies model. The majority of family policies in CEE countries suffer from a variety of shortcomings that impede them from generating enhanced family welfare and from providing conditions for cohort fertility to increase. The likely further decline of cohort fertility, or its stagnation, may entail long-term demographic as well as other societal consequences, such as continuous declines in total population numbers, changes in age structures, as well as implications for health and social security costs.